Ultraviolet Radiation Exposure from UV-Transilluminators - Akbar-Khanzadeh, Farhang; Jahangir-Blourchian, Mahdi (Journal of occupational and environmental hygiene, 2005)
UV-transilluminators use ultraviolet radiation (UVR) to visualize proteins, DNA, RNA, and their precursors in a gel electrophoresis procedure. This study was initiated to evaluate workers' exposure to UVR during their use of UV-transillumin- ators. The levels of irradiance of UV-A, UV-B, and UV-C were determined for 29 UV-transilluminators at arbitrary measuring locations of 6, 25, 62, and 125 cm from the center of the UV-transilluminator's filter surface in the direction of the operator's head. The operators (faculty, research staff, and graduate students) worked within 62 cm of the transilluminators, with most subjects commonly working at ≤25 cm from the UV-transilluminator's filter surface. Daily exposure time ranged from 1 to 60 min. Actinic hazard (effective irradiance level of UVR) was also determined for three representative UV-transilluminators at arbitrary measuring locations of 2.5, 5, 10, 15, 20, 30, 40, and 50 cm from these sets' filter surface in the direction of the operator's head. The allowable exposure time for these instruments was less than 20 sec within 15 cm, less than 35 sec within 25 cm, and less than 2 min within 50 cm from the UV-transilluminators' filter surface. The results of this study suggest that the use of UV-transilluminators exposes operators to levels of UVR in excess of exposure guidelines. It is recommended that special safety training be provided for the affected employees and that exposure should be controlled by one or the combination of automation, substitution, isolation, posted warning signs, shielding, and/or personal protective equipment.